Enhancing Social Studies Learning Motivation Through Quizizz-Based Technology - Mohd Fadlan Riski; Toni Nasution (MASI Mandiri Edukasi, 2025)
This study examines whether Quizizz-based learning enhances students’ motivation in social studies, addressing the limited integration of gamified tools in Indonesian classrooms. Employing a quantitative experimental method with a post-test-only control group design, the research involved two randomly selected seventh-grade classes at SMP 1 Southeast Aceh. One class served as the experimental group using Quizizz-based learning, while the other functioned as the control group with conventional teaching methods. The sample consisted of 39 students—19 in the experimental group and 20 in the control group. Data were collected through post-test assessments measuring students' interest and engagement in learning. The results indicate a significant difference in learning engagement between the two groups. The experimental group achieved an average score of 90.78, while the control group averaged 61.05. An independent sample t-test yielded a t-value of 5.3693, exceeding the critical value of 1.684 at the 5% significance level (p < 0.05), confirming a statistically significant effect. These findings suggest that Quizizz-based learning positively influences student engagement in social studies. This study underscores integrating interactive digital tools to create a more engaging learning environment. It is recommended that educators incorporate platforms like Quizizz to foster active participation and enhance learning experiences. Future research should explore long-term impacts across diverse subjects and educational settings to broaden the applicability of gamified learning strategies in Indonesian education.